HUBUNGAN ANTARA BEBAN KERJA DAN STRES KERJA DENGAN KUALITAS TIDUR PERAWAT INSTALASI GAWAT DARURAT - Situmeang, Lamria; Kadir, Abd; Saputra, M. Khalid Fredy; Yulis, Rahma; Werdini, Yoessy Etna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Poor sleep quality is a condition where, when someone is sleeping, they feel the desire to wake up from sleep as soon as possible. Workload and work stress have an important effect on sleep quality in nurses. The purpose of the study was to determine the relationship between workload and work stress with the quality of sleep of emergency department nurses. The type of research is quantitative with a cross sectional design. The research was conducted at PKU Muhammadiyah Gombong Hospital in July 2022. The research sample was nurses in the Emergency Department of PKU Muhammadiyah Gombong Hospital, totaling 41 with the sampling technique using total sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between workload (p value: 0.002) and work stress (p value: 0.000) with sleep quality in nurses. It is recommended for nurses to make the best use of rest time before work, such as doing sleep hygiene by limiting food and drinks before bed, starting to sleep and waking up at the same time, limiting napping hours, creating special rituals before bed, creating a comfortable sleeping environment, and exercising regularly in the morning or afternoon.